Entrepreneurial Leadership And Its Relationship With Organizational Excellence In Government Schools In Dammam - Nouf Manahi Zamil AL-Shahrani , Adel Al-Dhuwaihi (Migration Letters, 2024)
The study aimed to identify the degree of entrepreneurial leadership practice by female principals of public schools in the city of Dammam, the degree of organizational excellence achievement in their schools, and the relationship between them from their point of view. To achieve the study’s objectives, the correlational descriptive survey approach and the questionnaire tool were used to collect data. The study population consisted of all (149) female principals of public schools in Dammam. The study sample consisted of (108) female principals. The data were statistically processed using the Statistical Packages for Social Sciences (SPSS) in light of the study questions. The study revealed a set of results, most notably: The degree of entrepreneurial leadership practice [1]by the female principals of public schools in Dammam from their point of view was (high) with a mean of (4,05), and the order of dimensions was as follows: Creativity, initiative, risk-taking, strategic vision. The degree of institutional excellence achievement among the female principals of public schools in the city of Dammam was (high), where the general mean of the degree of achievement was (3,69) and the order of dimensions was as follows: School Leadership, Learning Outcomes, Teaching and Learning, School Environment. The findings revealed a correlation between the average degrees of female principals in Dammam public schools regarding entrepreneurial leadership practice and institutional excellence achievement degrees. Based on the findings, several recommendations and proposals were made.